1994
DOI: 10.1093/clinids/18.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Fungemia and Colonization with Nystatin-Resistant Candida rugosa in a Burn Unit

Abstract: Yeast isolates from burned patients were analyzed retrospectively for a 7-year period (1984-1991). Topical nystatin was used routinely in the burn wound dressing as antifungal therapy beginning in July 1986. Nystatin used was associated with a significant decrease in overall yeast acquisitions in burn wounds; yeasts were isolated from 15.5% of admitted patients before the use of nystatin vs. 10.5% with use of nystatin (odds ratio [OR] = 0.64; 95% confidence interval [CI], 0.48-0.86). New acquisitions of Candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
1
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 22 publications
1
49
1
5
Order By: Relevance
“…In vitro sensitivity reported 40.5% and 61.4% susceptibility to fluconazole and voriconazole respectively [1] . The occurrence of fatal breakthrough infection with C. rugosa in patients on amphotericin B is in contrast to observations of favourable susceptibility reports to amphotericin B, flucytosine and voriconazole [5]- [7] . In our experience, successful management was done with amphotericin B in the present case.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…In vitro sensitivity reported 40.5% and 61.4% susceptibility to fluconazole and voriconazole respectively [1] . The occurrence of fatal breakthrough infection with C. rugosa in patients on amphotericin B is in contrast to observations of favourable susceptibility reports to amphotericin B, flucytosine and voriconazole [5]- [7] . In our experience, successful management was done with amphotericin B in the present case.…”
Section: Discussioncontrasting
confidence: 63%
“…Resistance to nystatin was apparent in a study reporting 15 episodes of candidaemia due to C.rugosa following topical nystatin in a burn unit [7] . In vitro sensitivity reported 40.5% and 61.4% susceptibility to fluconazole and voriconazole respectively [1] .…”
Section: Discussionmentioning
confidence: 99%
“…Fungemia due to this species of Candida was unrecognized prior to 1985, when catheterrelated fungemia was reported in two different institutions in the United States (15,21). Subsequently, Dube et al (3) reported 15 episodes of candidemia due to C. rugosa in burn patients receiving topical nystatin treatment in a U.S. hospital. No obvious source of the infections was found; however, the isolates were shown to be resistant to nystatin and to have reduced susceptibility to both amphotericin B and fluconazole.…”
mentioning
confidence: 99%
“…The reason for these concordant observations of widespread prevalent genotypes among epidemiologically unrelated yeast strains is still unknown. Redkar et al [32] described a type of C. rugosa isolates to be predominant in burn patients, consistent with the theory that pathogenic isolates of this yeast species have emerged and persisted because of extensive use of topical nystatin [33]. It is known that the prophylactic use of ketoconazole in neutropenic patients may result in the emergence of a higher prevalence of C. glabrata among surveillance cultures [5].…”
Section: Discussionmentioning
confidence: 73%